2017
DOI: 10.3390/bioengineering4020044
|View full text |Cite
|
Sign up to set email alerts
|

Comparative N-Glycosylation Analysis of the Fc Portions of a Chimeric Human Coagulation Factor VIII and Immunoglobulin G1

Abstract: Prevention and treatment of bleeding in patients suffering from hemophilia A are inconvenient due to repeated intravenous infusions owing to the short half-life of coagulation factor VIII (FVIII) in circulation. Besides (glyco-)pegylation of the FVIII molecule, a bioengineering approach comprises the protein fusion to Fc-immunoglobulin (Ig)G that mediate protection from clearance or degradation via binding to the neonatal Fc receptor. While human-like N-glycosylation of recombinant FVIII is known to be crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The Fc Asn 297 is glycosylated but is within the core of the Fc dimer. Non-glycosylated Fc remains stable and folds properly, but the dimer formed by Fc domains lacking Asn 297 glycosylation has a tighter conformation, and this can reduce FcRn binding by ~10 fold 56 . Plant and metazoan glycosylation differ 57 , leading to possibly diminished FcRn binding and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The Fc Asn 297 is glycosylated but is within the core of the Fc dimer. Non-glycosylated Fc remains stable and folds properly, but the dimer formed by Fc domains lacking Asn 297 glycosylation has a tighter conformation, and this can reduce FcRn binding by ~10 fold 56 . Plant and metazoan glycosylation differ 57 , leading to possibly diminished FcRn binding and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…47 Interestingly, Kannicht et al showed that the Fc domain of rFVIII-Fc contains a remarkably low level of sialylation (less than 1%). 48 In contrast, the sialylation degree of the Fc domain of plasma-derived human IgG's is around 13%. 49 Thus, it can be speculated, that the very low sialic acid content of the fusion construct (and the abolishment of binding to sialic acid-specific receptors) in combination with the binding to FVIII-specific receptors and a co-ligation with FcgRIIa supports signaling pathways that drive DC activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, terminal sialylation of the Fc domain has been shown to be important for the anti‐inflammatory activity of IgG's, 45,46 probably by promoting an anti‐inflammatory milieu through the interaction with sialic acid recognizing receptors 47 . Interestingly, Kannicht et al showed that the Fc domain of rFVIII‐Fc contains a remarkably low level of sialylation (less than 1%) 48 . In contrast, the sialylation degree of the Fc domain of plasma‐derived human IgG's is around 13% 49 .…”
Section: Discussionmentioning
confidence: 99%
“…72 Despite recent rapid progress in the organon-a-chip model, a lot of devices are still complex to fabricate and integrated genetic quantification is quite difficult in these systems. 73,74 Through continued development and advancement, this approach will lead to powerful in-vitro pre-clinical cancer models that can facilitate the discovery of anti-cancer drugs.…”
Section: Applications Of Patient-derived In-vitro Cancer Model: Organ-on-a-chipmentioning
confidence: 99%